Effect of Positioning on Oxygen Saturation Among Neonates with Respiratory Distress - Kalsoom Shahnawaz Lashari; Lashari, Shaista Gul; Abdul Hameed Radhan; Zamir Ahmed Qambrani; Khuda Bux Khoso; Farzana Shaikh (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the impact of the prone position versus the supine position on oxygen saturation (SpO2) in children with respiratory distress. Study design: Qausi-experimental study Place and Duration of Study: Department of Pediatrics, Liaquat University of Medical Health Sciences (LUMHS), Jamshoro, Pakistan, from Apr to Sep 2025. Methodology: The study enrolled a sample size of 100 neonates, who were admitted to the neonatal intensive care unit (ICU) with respiratory distress. Following the initial stabilization, all the neonates were subjected to supplementary oxygen in both supine and prone positions. Demographic and clinical data were gathered. Statistical analysis was done through Statistical Package For Social Sciences (SPSS) version 27.00 with independent sample t-test to compare the mean SpO2 between positions where a p-value <0.05 was taken as significant. Results: The infants in the prone positioning group gradually experienced an increase in mean SpO₂, which reached 95.02 ± 2.15% at 90 minutes, while the supine group’s values stayed close to the baseline. A larger number of infants in prone position were able to get SpO₂ ≥92% starting from the 30-minute mark (p < 0.001), which proved that there was a continuous and statistically significant improvement in their oxygenation. Conclusion: Prone position had a significant positive effect in terms of oxygen saturation in neonates with respiratory distress as compared to the supine posture.